(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines multigenerational narratives as a complex literary form located at the intersection of genealogy, narratology, and cultural memory. It argues that such narratives function not only as representations of family continuity but as structural systems organizing temporality, identity, and historical experience. The study highlights how genealogical succession becomes narrative architecture and reveals tensions between continuity and rupture across generations.